The mental health status of children who have been evacuated or migrated from rural areas in Fukushima prefecture after the Fukushima daiichi nuclear power station accident:results from the Fukushima health management survey - Tokunaga, Akiko; Yoshida, Koji; Orita, Makiko; Urata, Hideko; Itagaki, Shuntaro; Mashiko, Hirobumi; Yabe, Hirooki; Maeda, Masaharu; Oishi, Kazuyo; Inokuchi, Shigeru; Iwanaga, Ryoichiro; Tanaka, Goro; et al. (FUKUSHIMA JOURNAL OF MEDICAL SCIENCE, 2020)
Introduction:We evaluated the mental health status of children residing in Kawauchi village (Kawauchi), Fukushima Prefecture, after the 2011 accident at the Fukushima Daiichi Nuclear Power Station, based on the children’s experience of the nuclear disaster.Methods:We conducted this cross-sectional study within the framework of the Fukushima Health Management Survey (FHMS);FHMS data on age, sex, exercise habits, sleeping times, experience of the nuclear disaster, and the “Strengths and Difficulties Questionnaire (SDQ)” scores for 156 children from Kawauchi in 2012 were collected. Groups with and without experience of the nuclear disaster — “nuclear disaster (+)” and “nuclear disaster (−)” — were also compared.Results:Our effective response was 93 (59.6%);the mean SDQ score was 11.4±6.8 among elementary school-aged participants and 12.4±6.8 among junior high school-aged ones. We statistically compared the Total Difficulties Scores (TDS) and sub-item scores of the SDQ between “elementary school” and “junior high school” or “nuclear disaster” (+) and (−). There was no significant difference between these items.Conclusions:We found indications of poor mental health among elementary and junior high school-aged children in the disaster area immediately following the accident, but no differences based on their experience of the nuclear disaster. These results indicate the possibility of triggering stress, separate to that from experiences related to the nuclear disaster, in children who lived in affected rural areas and were evacuated just after the nuclear disaster.